Initial antihypertensive agent effects on acute blood pressure after intracerebral haemorrhage. Issue 5 (20th April 2022) - Ng, Yisi; Qi, Wenjing; King, Nicolas Kon Kam; Christianson, Thomas; Krishnamoorthy, Vijay; Shah, Shreyansh; Divani, Afshin; Bettin, Margaret; Coleman, Elisheva R; Flaherty, Matthew L; Walsh, Kyle B; Testai, Fernando D; et al.
Abstract : Introduction: Current guidelines recommend blood pressure (BP) lowering in patients after acute intracerebral haemorrhage (ICH) without guidance on initial choice of antihypertensive class. This study sought to determine if initial antihypertensive class differentially effects acute BP lowering in a large multiethnic ICH cohort. Methods: Subjects enrolled in the Ethnic/Racial Variations in ICH study between August 2010 and August 2017 with elevated admission BP and who received labetalol, nicardipine or hydralazine monotherapy as initial antihypertensive were analysed. Primary outcomes were systolic and diastolic BP changes from baseline to first BP measurement after initial antihypertensive treatment. Secondary outcomes included haematoma expansion (HE), hospital length of stay (LOS) and modified Rankin Score (mRS) up to 12 months after ICH. Exploratory outcomes assessed effects of race/ethnicity. Linear and logistic regression analyses, adjusted for relevant covariates, were performed to determine associations of antihypertensive class with outcomes. Results: In total, 1156 cases were used in analyses. Antihypertensive class was associated with diastolic BP change (p=0.003), but not systolic BP change (p=0.419). Initial dosing with nicardipine lowered acute diastolic BP than labetalol (least square mean difference (labetalol-nicardipine)=5.47 (2.37, 8.57), p<0.001). Initial antihypertensive class was also found to be associated with LOS (p=0.028), but not with HE (p=0.406), mortality (p=0.118), discharge disposition (p=0.083) or mRS score at discharge, 3, 6 and 12 months follow-up (p=0.262, 0.276, 0.152 and 0.36, respectively). Race/ethnicity variably affected multivariable models. Conclusion: In this large acute ICH cohort, initial antihypertensive class was associated with acute diastolic, but not systolic, BP-lowering suggesting differential effects of antihypertensive agents. Trial registration number: NCT01202864 .